Gender, violence and attitudes: lessons from early modern Europe - Lidman, Satu (Routledge, Taylor & Francis Group, 2018)
"Gender, Violence and Attitudes explores the history of gender-based violence in early modern Europe, particularly intimate-partner violence and sexual violence. This book also investigates the legacy of gender-based violence through the Enlightenment to the present day. It offers historical background for highly topical human rights issues. Offering detailed analysis of gender and the culture of violence, Gender, Violence and Attitudes is essential reading for students and general readers who wish to understand the history of violence and its continual association with gender from early modern Europe to the present day"--